Depth heterogeneity of soil organic carbon dynamics in a heavily grazed alpine meadow on the northeastern Tibetan Plateau: A radiocarbon‐based approach. Issue 7 (21st July 2017) - Yu, Shi‐Yong; He, Honglin; Cheng, Peng; Hou, Zhanfang
Abstract: A deep understanding of soil organic carbon (SOC) dynamics on the Tibetan Plateau is crucial for predicting the response of the alpine carbon pool to future climate changes. Here we present information about SOC stocks and turnover time in a heavily grazed alpine meadow on the Tibetan Plateau based on radiocarbon ( 14 C) measurements and inverse modeling. Our results reveal that the alpine meadow soil is composed of three distinct carbon pools. The topsoil represents the active carbon pool, which has a carbon inventory‐weighted mean turnover time of 64 years. The CO2 efflux due to the mineral soil respiration from this pool is approximately 48.45 g C m −2 yr −1, accounting for 91% of the total heterotrophic soil respiration. The intermediate carbon pool has an inventory‐weighted mean turnover time of 780 years, and the rate of mineral soil respiration in this pool is an order of magnitude lower than that in the active carbon pool. The parental materials feature the passive carbon pool, which has millennia‐long turnover time and the mineral soil respiration is trivial. Comparing our results with other 14 C‐based studies suggests that grazing intensity may alter not only the SOC stocks but also the soil respiration rate in the alpine grassland ecosystem. The heavily grazed alpine meadow broadly fits the exponential relationship between turnover time and mean annual air temperature identified by meta‐analysis of published data from the Tibetan Plateau, alpine grassland, and forest sites elsewhere. Key Points: Mineral soil respiration accounts for 20% of total soil respiration in a heavily grazed alpine meadow on the northeastern Tibetan Plateau The heavily grazed alpine meadow broadly fits the exponential relationship between turnover time and mean annual air temperature identified by meta‐analysis of 50 sites The alpine grasslands on the Tibetan Plateau are under stress of climate warming and grazing